Healthcare practitioners as accomplices: a qualitative study of gender affirmation in a context of ambiguous regulation in Indonesia - Benjamin Hegarty; Alegra Wolter; Amalia Puri Handayani; Kevin Marian; Jamee Newland; Dede Oetomo; Ignatius Praptoraharjo; Angela Kelly-Hanku (BMC Medical Ethics)
Abstract Background The World Professional Association for Transgender Health guidelines Standards of Care 8 draw on ethical arguments based on individual autonomy, to argue that healthcare and other professionals should be advocates for trans people. Such guidelines presume the presence of medical services for trans people and a degree of consensus on medical ethics. Very little is known, however, about the ethical challenges associated with both providing and accessing trans healthcare, including gender affirmation, in the Global South. In light of the challenges associated with medical and legal gender affirmation in Indonesia, we conducted a qualitative study to understand the views of trans people, healthcare providers, and legal practitioners. Methods In this qualitative study, we drew on a participatory methodology to conduct 46 semi-structured interviews between October and December 2023, with trans people (10 trans feminine people and 10 trans masculine people, each interviewed twice) and key informants (three healthcare providers and three lawyers and paralegals). Trans people were a central part of the research team from inception through to analysis and writing. Participants were recruited via community-led sampling. Data analysis of interview data took place through an immersion/crystallisation technique and preliminary inductive coding which highlighted key quotes. We focused on an inductive analysis using participant narratives to identify key concepts in the ethics of gender affirmation in Indonesia. Results We characterize the ethics of supportive healthcare workers, community members, and family members, as that akin to “accomplices,” a concept of ethics used in theories of racial justice which evaluate a willingness to support people to navigate laws and regulations which perpetuate injustices and violence. Overall, both trans people and key informants shared an understanding that the legal status of gender-affirming medical care was particularly ambiguous in Indonesia due to a lack of clarity in both laws and regulations. For trans participants, ethical arguments for the validity of legal and medical gender affirmation was premised on evidence that their gender identity and expression was already recognized within society, even if limited to immediate friends and family. Given that all participants expressed a desire for gender affirmation, but such services were widely unavailable, accomplices played a crucial role in supporting trans people to access healthcare. Conclusions An empirical study based on an “ethics from below” helps to show that arguments grounded in autonomy, or based on biomedical evidence, are unlikely to alter unjust laws or facilitate a change to pathologizing guidelines governing understanding of trans people’s healthcare and legal needs in Indonesia. We provide an analysis that is sensitive to the ethics of facilitating gender affirmation in a context where that process is inherently social, and often articulated in relation to a prevailing religious morality.